Balancing Outcome vs. Urgency in Modern Liver Transplantation - Dancs, Peter T.; Saner, Fuat H.; Benkö, Tamas; Molmenti, Ernesto P.; Büchter, Matthias; Paul, Andreas; Hoyer, Dieter P. (Frontiers in Surgery, 2022)
Background: Current allocation mechanisms for liver transplantation (LT) overemphasize emergency, leading to poorer longtime outcomes. Utility was introduced to recognize outcomes in allocation. Recently, Molinari proposed a predictive outcome model based on recipient data. Aims: The aims of this study were to validate this model and to combine it with utility to emphasize outcome in allocation. Methods: We retrospectively analyzed 734 patients transplanted between January 2010 and December 2019. Points were assigned as in Molinari’s model, and score sum was correlated with observed 90-day mortality. Utility was calculated as the product of 1-year survival times 3-month mortality on the waiting list. Weighting of different compounds was introduced, and utility curves were calculated. MELD scores according to maximal utility were determined. Results: 120 patients (16.3%) died within 90 days after LT. Higher MELD score, obesity, and hemodialysis prior to LT were confirmed risk factors. Overall survival was 83.8% and 77.4% after 90 days and 12 months, respectively. General utility culminated at MELD scores >35 in the overall population. Emphasizing outcome shifted the maximal utility to lower MELD scores, depending on Molinari scores. Conclusions: Emphasizing outcome, at least in certain recipient risk categories, might improve the longtime outcomes and might be integrated into allocation models.